2019
DOI: 10.1007/s12035-018-1456-3
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2A-Cannabinoid CB1 Receptor Heteromers in the Hippocampus: Cannabidiol Blunts Δ9-Tetrahydrocannabinol-Induced Cognitive Impairment

Abstract: At present, the clinical interest on the plant-derived cannabinoid compound cannabidiol (CBD) is exponentially rising, since it displays multiple therapeutic properties. In addition, CBD can counteract the undesirable effects of the psychoactive cannabinoid Δ⁹-tetrahydrocannabinol (Δ⁹-THC) that dampen the clinical development of cannabisbased therapies. Despite this attention, the CBD mechanism of action and its interaction with Δ⁹-THC are still not completely elucidated. Here, by combining in vivo and molecul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 45 publications
0
30
0
Order By: Relevance
“…Importantly, unlike the present study, in the work by Aso et al (2019), all the drugs were systemically injected, and the antagonists were administered before memory acquisition. Consequently, interference with this memory phase cannot be excludedt.…”
Section: Discussionmentioning
confidence: 94%
“…Importantly, unlike the present study, in the work by Aso et al (2019), all the drugs were systemically injected, and the antagonists were administered before memory acquisition. Consequently, interference with this memory phase cannot be excludedt.…”
Section: Discussionmentioning
confidence: 94%
“…This suggests that CBD prevents oxidative stress by activating A 2A receptors. It was also shown that A 2A receptors can form heteromers with CB1 receptors in CA1 neurons and in the hippocampus of C57BL/6J mice [112]. Therefore, CBD can modify the functioning of the entire heteromer, and thus modulate the activation of two groups of receptors involved in the regulation of redox balance and inflammation.…”
Section: Adenosine a 2a Receptorsmentioning
confidence: 99%
“…100 Indeed, CBD was shown to downregulate inflammatory biomarkers and attenuate microglia activation in a viral mouse model of multiple sclerosis by interacting with A2a receptors. 99 Finally, it was suggested that CBD can blunt the THC-induced cognitive and memory impairments in an A2a receptor-dependent manner, 109 as shown by A2a receptor knockout mice performance in a two-object recognition test. 109 CBD is also known to act directly upon the 5-HT 1A receptor, which is found in the brain in large concentrations, with large densities at the prefrontal cortex, hippocampus, and amygdala.…”
Section: Cannabidiol Implications For Neuroprotection Following Concumentioning
confidence: 99%
“…99 Finally, it was suggested that CBD can blunt the THC-induced cognitive and memory impairments in an A2a receptor-dependent manner, 109 as shown by A2a receptor knockout mice performance in a two-object recognition test. 109 CBD is also known to act directly upon the 5-HT 1A receptor, which is found in the brain in large concentrations, with large densities at the prefrontal cortex, hippocampus, and amygdala. 110,111 CBD has been shown to exhibit a high potency for this receptor and serves as an agonist, to further stimulate the receptor's properties of decreasing anxiety, pain, and headaches.…”
Section: Cannabidiol Implications For Neuroprotection Following Concumentioning
confidence: 99%